Commercial imperatives and their implications on the community newspaper group: the case of the times and Masvingo star - Mandava, Peter (Midlands State University, 2015)
The paper explores principles that led to the birth of Zimbabwe Mass Media Trust [ZMMT] in general and its subsidiary, the Community Newspaper Group [CNG].The identity and performance of CNG s newspapers is examined. With special focus on The Times and Masvingo Star, the paper s thrust is CNG s transformation from being a rural public sphere to that of urban dwellers. Within the context of critical political economy of the media, and making references to forces that shaped the British working class press, the paper argues that, before its restructuring, the CNG had been an ailing group because of its weak capital base and managerial incompetence. Inadequate funding forced the CNG to operate with minimal provisions and a revised philosophy tilted in favor of urban readership that interests advertisers. Such commercial imperatives undermined the newspapers endevour to create a rural public sphere. Acceptance of business/commercial logic excluded rural folks in both coverage and distribution. The paper concludes that future rural press projects must have proper levels of initial capital, equipment and staffing so that there is no desperate craving for advertisers revenue for basic sustenance. This raises important questions about the role of the media in society generally and community media specifically in facilitating development support communication in a country like Zimbabwe.